2014
DOI: 10.1074/jbc.m114.566414
|View full text |Cite
|
Sign up to set email alerts
|

Altered Nucleosome Positioning at the Transcription Start Site and Deficient Transcriptional Initiation in Friedreich Ataxia

Abstract: Background: Friedreich ataxia (FRDA) is caused by an expanded GAA triplet repeat (GAA-TR) mutation that results in FXN transcriptional deficiency.Results: Repressive chromatin spreads from the expanded GAA-TR mutation, switching off the FXN gene promoter.Conclusion: Reduced transcriptional initiation is the major cause of FXN transcriptional deficiency in FRDA.Significance: Reactivation of FXN transcriptional initiation is a potential therapeutic strategy in FRDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…1A). In agreement with previous findings 11, 12 we noted a severe deficiency of FXN transcript in FRDA cells at both the upstream and downstream locations, supporting the existence of a major defect in transcriptional initiation (Fig. 1B).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1A). In agreement with previous findings 11, 12 we noted a severe deficiency of FXN transcript in FRDA cells at both the upstream and downstream locations, supporting the existence of a major defect in transcriptional initiation (Fig. 1B).…”
Section: Resultssupporting
confidence: 93%
“…12 Briefly, reverse transcription was performed either with a mixture of random hexamers and oligo dT primers (for the exon 3-4 amplicon) or with a strand-specific RT primer (for the exon 1 amplicon) using the QuantiTect ® reverse transcription kit (Qiagen). mRNA levels were quantified by real-time PCR relative to expression of the control TBP gene using the ΔΔCt method on the Eppendorf RealPlex-4 Mastercycler with SsoAdvanced ™ SYBR ® green supermix (BioRad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could answer questions regarding the chromatin structure associated with shorter-than-average expanded GAA triplet-repeats in FRDA, which is one of the definitive questions for the understanding of the pathogenesis of FRDA at the chromatin level [21]. However, several questions remain unclear.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The GAA triplet-repeats can also recruit heterochromatin-binding proteins. Further, the formation of heterochromatin on intron 1 of the FXN gene may trigger FXN gene silencing through an intrinsic blocking of transcription initiation or elongation [11,18,19,20,21,22,23,24,25,26,27]. Ruan et al found that the efficiency of nucleosome assembly on pure GAA 22 repeat duplex was only half that of the pUC control DNA.…”
Section: Accepted Manuscriptmentioning
confidence: 96%